Healing effects of Cornus mas L. in experimentally induced ulcerative colitis in rats: From ethnobotany to pharmacology - Suntar, Ipek; Cevik, Can Kerem; Ceribasi, Ali Osman; Gokbulut, Alper (Elsevier Ireland Ltd, 2020)
Ethnopharmacological relevance: The ethnobotanical studies conducted in Turkey and other countries have revealed that Cornus mas L., from the family Cornaceae have been used against stomachache, diarrhea and colitis. Aim of the study: The objective the present study is to determine the possible activity of C. mas in experimentally induced ulcerative colitis in rats and to identify its phytochemical feature. Materials and methods: 2,4,6-Trinitrobenzene sulfonic acid-induced colitis model was induced in rats. The rats were orally treated with different doses (50, 100, 200 and 400 mg/kg) of C. mas 80% methanol extract for 14 days. Increase in body weight, consumed amount of feed, form of the stool, presence of rectal prolapse were followed every day. At the end of the experiment, colon tissues were removed and wet weights for each animal were measured and colon damages were scored. Total antioxidant and total oxidant status, cytokine (TNF-alpha and IL-1 beta) and protein levels of colon tissues were evaluated and histopathological analyses were carried out. After the detection of the effective dose as 400 mg/kg, the aqueous methanol extract was fractionated by using liquid-liquid fractionation technique and the sub-extracts were also tested for in vivo biological activities. High Performance Liquid Chromatography analyses were conducted to determine the phytochemical profile of the active crude extract and n-butanol sub-extract. Results: Amount of feed consumed per day and increase in body weight were the lowest in the control group, while those values were determined to be the highest in 80% methanol extract (at 400 mg/kg dose), n-butanol sub-extract and reference groups. Following colitis induction, it was determined that the fecal form was yellow-slippery in all groups and returned to normal after the treatment with C. mas extracts. Rectal prolapse score was less in the extract (400 mg/kg) and n-butanol sub-extract treated groups. Total antioxidant, total oxidant status, cytokine and protein levels were found to be in parallel with macroscopic findings. 80% methanol extract (400 mg/kg) and n-butanol sub-extract provided the best healing according to the wet weight measurements and colon damage scoring performed on the removed colon tissues. These findings supported the results of histopathological analysis. According to the chromatographic analysis, ellagic acid was determined in both extracts and its amount was quantified. Conclusions: The present study has verified the ethnomedical use of C. mas for the treatment of ulcerative colitis.
Keywords: Corpus mas L.; Cornaceae; Ulcerative colitis; Ethnopharmacology; Trinitrobenzene sulfonic acid